2016
DOI: 10.1590/1807-3107bor-2016.vol30.0114
|View full text |Cite
|
Sign up to set email alerts
|

Validity of periodontitis screening questions in a Brazilian adult population-based study

Abstract: Population-based studies assessing self-reported periodontal questions in low-income countries are lacking, and therefore we aimed to assess the accuracy of self-reported periodontal items in Brazil. One thousand one hundred and forty adults from Florianópolis, Brazil, had their periodontium clinically examined, and responded to the following self-reported items on periodontal conditions: Question (Q)1, Do you have any wobbly teeth?; Q2, Do your gums usually bleed?; and Q3, Has your dentist ever told you that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Studies that evaluated self‐reported oral health measures to predict periodontitis have shown that a single question is not appropriate to determine periodontitis . However, self‐reported gum/teeth health, loose teeth and lost teeth presented herein individually combined values of sensitivity plus specificity that ranged from approximately 1.30 and 1.40.…”
Section: Discussionmentioning
confidence: 95%
“…Studies that evaluated self‐reported oral health measures to predict periodontitis have shown that a single question is not appropriate to determine periodontitis . However, self‐reported gum/teeth health, loose teeth and lost teeth presented herein individually combined values of sensitivity plus specificity that ranged from approximately 1.30 and 1.40.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, self-reports are an alternative to estimate the prevalence of periodontal disease when a complete clinical examination is not possible 20 and efforts have been made to validate this model in Brazil. 17 , 21 In the context of the National Fanconi Anemia Meeting (many individuals, no dental chair and short time) this represents a great opportunity to evaluate the oral condition of a representative sample of FA patients. Considering that in the present study the majority of participants presented unsatisfactory clinical conditions related to gingival inflammation, it is important to know if it is compatible with their self-perception to adopt strategies of oral hygiene support and dental care.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical relevance of the presence of periodontitis is questionable because no associations with common blood parameters were found in the current study. In recent literature, inhomogeneous findings regarding similar screening methods for periodontitis exist (Ng & Leung, ; Eke et al, ; Foster Page et al, ; Ramos et al, ). In principle, a clinical periodontal examination remains undesirable for exact periodontitis diagnosis (Foster Page et al, , Ramos et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent literature, inhomogeneous findings regarding similar screening methods for periodontitis exist (Ng & Leung, ; Eke et al, ; Foster Page et al, ; Ramos et al, ). In principle, a clinical periodontal examination remains undesirable for exact periodontitis diagnosis (Foster Page et al, , Ramos et al, ). However, standardised questionnaires are able to predict periodontal conspicuities well and are a promising approach, especially if clinical diagnostics are not available (Eke et al, ).…”
Section: Discussionmentioning
confidence: 99%